Pathological features of the lungs and liver of piglets under conditions of constant vaccination of livestock against circovirus infection - P. V. Burkov; P. N. Shcherbakov; M. A. Derkho; M. B. Rebezov; K. V. Stepanova; A. O. Derkho; A. N. M. Ansori (Теория и практика переработки мяса, 2023)
The pathogenicity of PCV 2 in the body of vaccinated piglets was studied based on the results of pathomorphological changes in the lungs and liver of animals. The work was carried out on commercial piglets vaccinated with the vaccine Ingelvak CircoFLEX (Germany) against circovirus. The work used clinical, zootechnical, enzyme immunoassay and pathomorphological research methods. It has been established that under the conditions of ongoing vaccination of piglets against PCV2, 30.3% of piglets still do not have virus-neutralizing antibodies. The main reason for the culling of animals are circovirus diseases that have respiratory clinical signs, as well as signs of multisystem wasting syndrome, determining the safety of the livestock at the level of 68.05%, the average live weight of 1 head at the moment of its transfer for fattening is 40.44±0.78 kg, and the average daily gain in live weight is 346.00±9.18 g. At autopsy, sick piglets reveal an increase in the lungs and liver, and the signs of inflammation in them, as a result of circulatory disorders, damage to the lymphoid tissue, the development of dystrophic and necrotic changes. The results of the research suggest that in order to increase the efficiency of the formation of post-vaccination immunity, specific medical preparations can be used to stimulate the immune response of the body, as well as to enhance the resistance of the lymphoid tissue of the lungs and liver in animals.